O processo histórico de ocupação da vila do Palheta - Muaná-PA: uma análise do trabalho, território e identidade - MEDEIRO, Ana Caroline Tavares de (2022)
Memories of the historical reconstruction of Vila do Palheta, located in Muaná-Pa. The research proposes to reconstruct the occupation history and record the memories of the residents of the village. The methodology adopted was in the form of semi-structured interviews, which were recorded, transcribed and analyzed with the theoretical focus, namely: Marc Bloch (2001), Maurice Halbwachs (1990), Michael Pollak (1992) and Le goff (2003), Roger Chartier (1999) and Carlo Ginzburg (1986), Luiz Reznik (2002), Milton Santos and Maria Laura Silveira (2006) who discuss temporality, memories, culture and territoriality, respectively. Thus, we can record the history of the village on paper and retrieve memories, but gaps left by the past still need to be answered. Soon, in order to recognize the history of the village, current residents will have access to the past of the village and the culture of the same will not be lost.